Effectiveness of percutaneous neuromuscular electrical stimulation for neck pain relief in patients with cervical spondylosis - Miao, Qiang (Medicine (Baltimore), 2018)
BACKGROUND: This study aimed to evaluate the effectiveness and safety of percutaneous neuromuscular electrical stimulation (PNMES) for treating neck pain in patients with cervical spondylosis (CS). METHODS: One hundred and twenty four patients with neck pain of CS were included, and then they were randomly divided into a PNMES group and a control group in a ratio of 1:1. All patients received PNMES or sham PNMES 30 minutes daily, 3 times weekly for 12 weeks. The primary outcome was assessed by the visual analog scale (VAS). The secondary outcomes were evaluated by the cervical range of motion (ROM), neck disability index (NDI) score, as well as the adverse events (AEs). All outcome measurements were measured at the end of 12-week treatment, and 4-week follow-up after treatment. RESULTS: At the end of the 12-week treatment, and 4-week follow-up, the patients receiving PNMES exhibited more decrease in the mean VAS (P < .01), and NDI (P < .01) respectively, compared with the patients receiving sham PNMES. Additionally, the increase in the mean ROM was also significantly higher in the PNMES group than that in the sham PNMES group at the end of the 12-week treatment, and 4-week follow-up, respectively (P < .01). No AEs were found in either group. CONCLUSIONS: The results of this study demonstrated that PNMES is more effective than Sham PNMES for neck pain relief in patients with CS.